Imagined Communities and Cultural Memory: The Role of Literature in Shaping National Identity and Collective Consciousness - Rashmi G.H. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Based on foundational concepts such as Benedict Anderson’s Imagined Communities, Jan and Aleida Assmann’s distinction between communicative and cultural memory, and Maurice Halbwachs’ theory of collective memory, alongside the latest research on digital memory formation (for instance, a shift from mnemonic objects to mnemonic assemblages in the digital age of collective memory, along with ethnographic studies and the phenomenon of “ruinated futurity” in the Dongbei literary renaissance in text above) this paper argues that literature preserves national identity by narrativizing shared pasts and symbols, gives voice to marginalised or silenced histories, enables intergenerational and transnational memory transmission, mediates between hegemonic official narratives and plural cultural identities, re-drawing the conceptual boundaries of inclusion and exclusion through myth, epic, and testimony, and despite also being remediated through multimedia and digital screens that provide broader input, agency, and reach, shaping imagined communities and collective consciousness in post-colonial, multicultural, and globalized contexts, so that national identity becomes rooted simultaneously in material culture and cultural memory and continually negotiated in reaction to contemporary socio-technical and political forces, and this dialectic also reflects literature’s crucial role in not only preserving identity but also fostering reflection, critique, and renewal among heterogeneous publics in the 21st century.